Ecology and threats to gorgonian corals :invasive species and disease outbreaks in the Tropical Eastern Pacific (2018)
Gorgonian corals (Anthozoa, Octocorallia) play paramount ecological roles in benthic communities. As these organisms are long-lived and slow-growing species, they are particularly sensitive to environmental conditions and disturbances, being among the most vulnerable reef organisms. However, gorgonian responses to environmental conditions and the effects of biotic and abiotic threats on their populations are poorly understood in unperturbed marine areas. This doctoral thesis studies abiotic factors such as local and global environmental conditions and biotic factors such as disease outbreaks and invasive species affecting Pacifigorgia cairnsi sea fans in Malpelo Island (Tropical Eastern Pacific), a marine remote area little affected by direct anthropogenic pressures. In order to assess P. cairnsi health state and to understand whether these threats may represent long-term impacts to their populations we have used several approaches including phylogeography, metabarcoding, microbial ecology and demography. Our results suggest that (1) Carijoa riisei might have been introduced from the Tropical Atlantic region into the Colombian TEP and it constitutes a fully invasive species in this region. Additionally, we found that (2) the bacterial microbiome associated with the "Necrotic Patch Disease" (NPD) behaves opportunistically and is likely in a state of microbial dysbiosis. Moreover, the confinement of the disease-related consortium to symptomatic tissues may facilitate colony recovery by tissue breakage. Finally, (3) P. cairnsi populations showed high densities, population size structures driven by local hydrodynamics, growth rates negatively affected by El Niño Southern Oscillation (ENSO) events and low NPD prevalence, while most of colonies recovered. Overall, we conclude that P. cairnsi develop mature and healthy populations at Malpelo Island but some threats such as invasive species and ENSO events may represent a long-term impact to these key benthic organisms